Treaty Rights, Political Recognition, and Indigenous Resource Access in the Obtawaing - Cottrell, Clifton (The International Indigenous Policy Journal, 2025)
To preserve access to key species, many tribes in the United States historically negotiated for usufruct rights in treaties. Treaties have taken on a renewed significance in the modern era as tribes seek to protect local resources and co-manage key species with state governments. This paper assesses the impact of treaty rights on resource access through a thematic identification study of important resource access characteristics for federally recognized tribes in Northern Michigan and the non-federally recognized Burt Lake Band of Ottawa and Chippewa Indians. While non-federal tribes can negotiate to ease some barriers to access with amicable local governments and landholders, treaty rights provide federal tribes with opportunities for regulatory control, enforcement, and an enhanced adaptive capacity to climate change.